2005
DOI: 10.1080/00207450590898481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Visual Evoked Potentials

Abstract: The aim of this study was to investigate the effects of acute or habitual exercise on visual evoked potentials (VEP). The study group consisted of 9 female and 7 male volleyball players and the control group contained 9 female and 7 male students who were not involved in any sportive activity. The N75, P100, and N145 latency and amplitudes were measured before and after exercise. Intragroup comparison was made to evaluate the acute effects and intergroup comparison for the chronic effects of exercise. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 12 publications
7
26
0
1
Order By: Relevance
“…So far researchers have mainly focused on investigating visual evoked potentials in groups of athletes and untrained individuals. The differences found for the parameters of the visual evoked potentials between professional athletes and non-athletes have indicated that adaptations of the visual functions in sports requiring rapid detection of and response to visual stimuli are possible [1,8,9,12]. The results of studies carried out by other authors have confirmed the influence of long-term sports training characterised by a high degree of involvement of perceptual functions on neuroanatomical changes in the brains of athletes practising different sports disciplines.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…So far researchers have mainly focused on investigating visual evoked potentials in groups of athletes and untrained individuals. The differences found for the parameters of the visual evoked potentials between professional athletes and non-athletes have indicated that adaptations of the visual functions in sports requiring rapid detection of and response to visual stimuli are possible [1,8,9,12]. The results of studies carried out by other authors have confirmed the influence of long-term sports training characterised by a high degree of involvement of perceptual functions on neuroanatomical changes in the brains of athletes practising different sports disciplines.…”
Section: Discussionsupporting
confidence: 75%
“…The research by Thomas et al [7] showed that cricket players had a shorter N75 wave latency than untrained subjects, whereas Delpont et al [8] observed a shorter latency of P100 waves in tennis and squash players compared to rowers and control subjects. Similar results were obtained in studies involving athletes practising such sports as volleyball [9,10], fencing [11], and karate [12]. These findings suggest that practising sports which are fastpaced and require accurate and rapid responses to visual stimuli can have a greater impact on the effectiveness of visual processing compared to undertaking other forms of sports training.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Increased neural efficiency (i.e., performing the same work with less cortical effort) has been demonstrated in athletes using electrophysiological techniques. However, the reverse effect has been reported for sensory stimuli processing (Murakami et al, 2008;Ö zmerdivenli et al 2005), and when attention and motor inhibition are required . These data can be interpreted as adaptive changes consequent to sports activity.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have revealed shortened VEP latencies in trained subjects compared to sedentary subjects (Ozkaya et al 2003;Ozmerdivenli et al 2005). Delpont et al (1997) found shortened patterned reversal visual evoked potential (PREP) latencies in a group of tennis players but found that they were unaltered in rowers compared to control subjects.…”
mentioning
confidence: 99%